1995
DOI: 10.1021/j100049a002
|View full text |Cite
|
Sign up to set email alerts
|

Reverse (Uphill) Electron Transfer at the Liquid/Liquid Interface

Abstract: Reverse electron transfer, in which an electron is transferred uphill from a redox couple with a higher standard reduction potential in one phase to another redox couple having a lower standard reduction potential in a second immiscible phase, is demonstrated using the system TCNQ (in 1,2-dichloroethane)/ferrocyanide (in water). The driving force for the reverse electron transfer is the presence of appropriate potential-determining ions that govern the interfacial potential difference, which in turn determines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 4 publications
2
56
0
Order By: Relevance
“…This led soon to development of various electrochemical techniques to study the liquid/liquid interface, including, among others, studies of the solvent dropping interface [103][104][105][106][107][108] , and studies of cyclic voltammetry 108 , impedance measurements [109][110][111][112] , drop pressure method 113 , galvanostatic pulse method 114,115 , stripping voltammetry 114 , voltfluorometry [116][117][118][119] , and transport across a microinterface [120][121][122][123][124][125] . Electron transfer and photoinduced electron transfer have been also observed on ITIES or theoretically treated 19,84,86,87,[126][127][128][129][130][131][132][133] , as well as electrochemical catalysis 19,126,127,134,135 , adsorption 15,72,[136][137]...…”
Section: When Nernstmentioning
confidence: 99%
“…This led soon to development of various electrochemical techniques to study the liquid/liquid interface, including, among others, studies of the solvent dropping interface [103][104][105][106][107][108] , and studies of cyclic voltammetry 108 , impedance measurements [109][110][111][112] , drop pressure method 113 , galvanostatic pulse method 114,115 , stripping voltammetry 114 , voltfluorometry [116][117][118][119] , and transport across a microinterface [120][121][122][123][124][125] . Electron transfer and photoinduced electron transfer have been also observed on ITIES or theoretically treated 19,84,86,87,[126][127][128][129][130][131][132][133] , as well as electrochemical catalysis 19,126,127,134,135 , adsorption 15,72,[136][137]...…”
Section: When Nernstmentioning
confidence: 99%
“…Using ferrocyanide and 7,7,8,8-tetracyanoquinodimethane ͑TCNQ͒, the forward and back rate constants for electron transfer between water and dichloromethane have been measured. 63,64 A SECM may be used to probe the redox activity of individual living cells and to measure the rate of transmembrane charge transfer. Significant differences were detected in the redox response given by normal human breast ephithelial cells and metastatic breast cancer cells.…”
Section: Industrial Processesmentioning
confidence: 99%
“…Based on these results, it was concluded that conventional electron transfer theories for the metal/electrolyte interface were applicable to liquid/liquid systems. Further work [73] demonstrated that interfacial electron transfer processes could be driven``uphill''. By poising the potential difference across a 1,2-dichloroethane (DCE)/water interface, with appropriate concentrations of potential determining ions in each phase, it was shown that an electron could be transferred from a redox couple in phase 1 to a second couple in phase 2, which had a lower standard reduction potential.…”
Section: Electron Transfer Kinetics Using the Feedback Modementioning
confidence: 99%